Nepal: Impacts of the Ukraine and global crises on poverty and food security - Xinshen Diao; Dorosh, Paul A.; Ellis, Mia; Pal, Barun Deb; Smart, Jenny; Takeshima, Hiroyuki; Thurlow, James (International Food Policy Research Institute, 2022)
Global food, fuel, and fertilizer prices have risen rapidly in recent months, driven in large part by the fallout from the ongoing war in Ukraine and the sanctions imposed on Russia. Other factors, such as export bans, have also contributed to rising prices. Palm oil and wheat prices increased by 56 and 100 percent in real terms, respectively, between June 2021 and April 2022, with most of the in-crease occurring since February (Figure 1).